Prediksi Jumlah Customer Di Bengkel H. Tomo Service Menggunakan Metode Backpropagation - Yusuf Afani; Magdalena Simanjuntak; Rusmin Saragih (Yayasan Kita Menulis, 2022)
A workshop is a building that provides space and equipment for carrying out construction or manufacturing, and repairing objects. The accumulation of customers at Bengkel H. Tomo Service is caused by the lack of workers in the repair process. This is based on not every day customers who come in excessive numbers, but at one time the situation is not crowded enough. Due to this condition, the number of repair workers is reduced so that the workshop owner can adjust between the customer and the worker. From these conditions, the H. Tomo Service Workshop needs to create a system that can predict the number of customers who will come in the following days or months. The prediction results can be used to anticipate the needs of repair workers in the workshop. The process of predicting the number of customers who make vehicle repairs at the workshop can be done with a computerized system, one of the processes that can be done is the application of an Artificial Neural Network (ANN) using the Backpropagation method. The system is designed with the MATLAB R2014a programming application, after carrying out the data training process and data testing on 2016 to 2020 data, the learning rate is 0.2; the maximun epoch is 10000 and the target error is 0.001, the result is that in 2021 the predicted number of customers is 13758 customers who make repairs at the H. Tomo Service workshop.